2017
DOI: 10.3389/fmicb.2017.02022
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Dynamics in Cyanobacteria Dominated Microbial Mats Measured by Novel Combined H2/H2S and H2/O2 Microsensors

Abstract: Hydrogen may accumulate to micromolar concentrations in cyanobacterial mat communities from various environments, but the governing factors for this accumulation are poorly described. We used newly developed sensors allowing for simultaneous measurement of H2S and H2 or O2 and H2 within the same point to elucidate the interactions between oxygen, sulfate reducing bacteria, and H2 producing microbes. After onset of darkness and subsequent change from oxic to anoxic conditions within the uppermost ∼1 mm of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Moreover, H 2 microsensors are sensitive (detection limit generally < 1 μM), fast responding (response time of a few seconds), highly accurate and almost non-invasive [14,15]. Microsensors for H 2 have been used for many years to study different natural environments on a microscale [16,17]. Since bioelectrochemical and other biotechnologies are nowadays intensively being studied, H 2 microsensors are also being used to obtain insights into engineered systems [8,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, H 2 microsensors are sensitive (detection limit generally < 1 μM), fast responding (response time of a few seconds), highly accurate and almost non-invasive [14,15]. Microsensors for H 2 have been used for many years to study different natural environments on a microscale [16,17]. Since bioelectrochemical and other biotechnologies are nowadays intensively being studied, H 2 microsensors are also being used to obtain insights into engineered systems [8,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Migratory rhythms determined by day/night cycles, UV exposure and changes in irradiance levels have been described for both microalgae and cyanobacteria‐dominated phototrophic mat communities (Haro et al, 2019; Lichtenberg et al, 2020). During the night, due to a continuing sulfate reduction in the absence of oxygenic photosynthesis, the mats changed to anoxic conditions and with high hydrogen sulfide concentration (Maegaard et al, 2017; Nielsen et al, 2015). Daily variations, such as the day – night cycle, are thought to have little influence on the composition of coastal microbial mat communities, although they may enhance or suppress the metabolic activity of different populations (Campbell et al, 2020; Haro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we show how the problem of difficult alignment of microsensors for the study of H 2 S oxidation can be solved. It has earlier been shown that a single sensor can be used for simultaneous and spatially coincident measurement of O 2 /N 2 O (Revsbech et al 1988), H 2 /O 2 (Maegaard et al 2017), and H 2 /H 2 S (Maegaard et al 2018). We here expand this range of combined sensors with a sensor for measuring H 2 S and O 2 .…”
mentioning
confidence: 99%